2020
DOI: 10.1029/2019ea000865
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Resolving WRF Simulations of Precipitation and Soil Moisture Over the Central Tibetan Plateau: An Assessment of Various Physics Options

Abstract: The evaluation of the regional climate model is of great importance for model's developments and applications. We assessed the performance of Weather Research and Forecasting (WRF) cloud resolving simulations with various physics options in terms of precipitation and soil moisture over the central Tibetan Plateau (TP) for a 2‐month simulation from July to August in 2015. The simulated precipitation is most sensitive to the microphysics scheme, followed by the land surface model, which plays a vital role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 67 publications
(104 reference statements)
0
22
0
Order By: Relevance
“…They also found that convection‐permitting model which explicitly resolve the deep convection process outperforms convection‐parameterization schemes models in the summer mean precipitation amount, frequency and intensity over the Tibetan Plateau. The choice of microphysics schemes and land surface model, as well as the ability to resolve orographic drag and mountain‐valley circulation over complex terrain could also influence the precipitation simulation over the Tibetan Plateau and surrounding area (Lin et al, 2018; Lv et al, 2020). Therefore, more realistic parameterization or explicit description of different rainfall‐relevant processes are needed in the future model development (Trenberth et al, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…They also found that convection‐permitting model which explicitly resolve the deep convection process outperforms convection‐parameterization schemes models in the summer mean precipitation amount, frequency and intensity over the Tibetan Plateau. The choice of microphysics schemes and land surface model, as well as the ability to resolve orographic drag and mountain‐valley circulation over complex terrain could also influence the precipitation simulation over the Tibetan Plateau and surrounding area (Lin et al, 2018; Lv et al, 2020). Therefore, more realistic parameterization or explicit description of different rainfall‐relevant processes are needed in the future model development (Trenberth et al, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Wang et al (2020) demonstrated that a WRF with 3 km grid spacing considerably reduced wet biases over the central Himalayas. Lv et al (2020) used the WRF to conduct a 2-month simulation to test different model physical configurations over the central TP. They found that the simulated precipitation frequency is dominated by the microphysics scheme and the simulated soil moisture is most sensitive to the land surface model.…”
Section: Introductionmentioning
confidence: 99%
“…The synergy of orographic drag parameterization and finer resolution can further greatly reduce biases of WRF-simulated precipitation in central Himalaya (Wang, Yang, et al, 2020). Furthermore, recent studies have proven that the simulation with convection-permitting resolution improves accuracy in simulating the seasonal or diurnal cycle of precipitation over TP (Li et al, 2020(Li et al, , 2021Lv et al, 2020;Ou et al, 2020;Zhou et al, 2021). Wang, Tolksdorf, et al (2020) showed that the simulated temperature can be improved by correcting the initial snow depth in WRF.…”
mentioning
confidence: 99%